2006
DOI: 10.1111/j.1365-2222.2006.02640.x
|View full text |Cite
|
Sign up to set email alerts
|

Inverse association of farm milk consumption with asthma and allergy in rural and suburban populations across Europe

Abstract: Our results indicate that consumption of farm milk may offer protection against asthma and allergy. A deepened understanding of the relevant protective components of farm milk and a better insight into the biological mechanisms underlying this association are warranted as a basis for the development of a safe product for prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
187
5
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(196 citation statements)
references
References 35 publications
2
187
5
2
Order By: Relevance
“…Consumption of unpasteurized farm milk in farmers' and nonfarmers' children has also been shown to be protective in several of the farmers' studies [10,14,17,56,57]. The etiological mechanisms are unclear, but probiotic bacteria or other currently unidentified non-microbial components in farm milk may play a role.…”
Section: Protective Exposuresmentioning
confidence: 99%
“…Consumption of unpasteurized farm milk in farmers' and nonfarmers' children has also been shown to be protective in several of the farmers' studies [10,14,17,56,57]. The etiological mechanisms are unclear, but probiotic bacteria or other currently unidentified non-microbial components in farm milk may play a role.…”
Section: Protective Exposuresmentioning
confidence: 99%
“…Exposure to pesticides has also been associated with many respiratory symptoms including sinus problems [3,9]. On the other hand, several studies have identified some of the exposures associated with a farming lifestyle that contributed to the reduced risk of rhinitis, asthma, and allergic diseases in farm children (i.e., contact with livestock; contact with animal feed such as hay, grain, straw, and silage; and the consumption of unprocessed cow's milk) [1,4,5,[10][11][12][13][14][15]. The reduced risk in farm children has been attributed to higher endotoxin levels and more diverse exposures to microbial components in the farm environment [1,4,[10][11][12]15].…”
Section: Introductionmentioning
confidence: 99%
“…Interventions with supplementation of a single nutrient have been disappointing (3)(4)(5), and it may be important to consider the diet as a whole to understand the possible synergistic effects of various food components. Several studies have shown that asthma outcomes were negatively associated with citrus fruits (6), apples, pears (7)(8)(9), tomato, carrots, leafy vegetables (7), butter, whole milk (9) and nonpasteurized farm milk (10), and positively associated with fast foods (11). However, studies addressing the associations between different dietary patterns and asthma are still lacking.…”
mentioning
confidence: 99%